2016
DOI: 10.1016/j.vaccine.2015.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a cytomegalovirus glycoprotein B (gB) vaccine in adolescent girls: A randomized clinical trial

Abstract: Background Cytomegalovirus (CMV) is a leading cause of congenital infection and an important target for vaccine development. Methods CMV seronegative girls between 12 and 17 years of age received CMV glycoprotein B (gB) vaccine with MF59 or saline placebo at 0, 1 and 6 months. Blood and urine were collected throughout the study for evidence of CMV infection based on PCR and/or seroconversion to non-vaccine CMV antigens. Results 402 CMV seronegative subjects were vaccinated (195 vaccine, 207 placebo). The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
185
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 22 publications
2
185
1
2
Order By: Relevance
“…Drawing upon standard vaccine strategies, the HCMV field has previously attempted to induce potent antiviral immunity by various approaches including attenuation of live viruses (8)(9)(10), formulation of HCMV glycoprotein subunit vaccines (11)(12)(13), use of viral vectors for epitope expression (14)(15)(16), and delivery of single and bivalent DNA plasmid vaccines (17,18). However, our understanding of anti-HCMV humoral immunity is complicated by the number of distinct glycoprotein complexes that contain neutralizing epitopes, most notably glycoprotein B (gB; fusion protein) and the pentameric complex gH/gL/UL128-131A (PC; necessary for entry into epithelial/endothelial cells) (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing upon standard vaccine strategies, the HCMV field has previously attempted to induce potent antiviral immunity by various approaches including attenuation of live viruses (8)(9)(10), formulation of HCMV glycoprotein subunit vaccines (11)(12)(13), use of viral vectors for epitope expression (14)(15)(16), and delivery of single and bivalent DNA plasmid vaccines (17,18). However, our understanding of anti-HCMV humoral immunity is complicated by the number of distinct glycoprotein complexes that contain neutralizing epitopes, most notably glycoprotein B (gB; fusion protein) and the pentameric complex gH/gL/UL128-131A (PC; necessary for entry into epithelial/endothelial cells) (19).…”
Section: Introductionmentioning
confidence: 99%
“…to reach target endpoints in human clinical trials, the HCMV gB subunit vaccine demonstrated moderate (~50%) efficacy at preventing primary HCMV infection, which is promising for future vaccine-development efforts (12,13). Additional retrospective human studies have reported that neutralizing antibodies targeting HCMV surface glycoproteins are correlated with reduced incidence of congenital virus transmission after primary maternal HCMV infection (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study of gB/MF59 was conducted in healthy seronegative adolescent girls [69]. This Phase II study was designed to determine safety and efficacy with an end point based on evidence of HCMV infection.…”
Section: Human Trials Of Subunit Gb Vaccinementioning
confidence: 99%
“…Boosting of gB-specific cell-mediated immunity and antibody responses to gB [69] Bernstein et al (2016) Phase II study (gB/MF59 placebo controlled):…”
Section: Hcmv-seropositive Adult Womenmentioning
confidence: 99%
See 1 more Smart Citation